Biomimetic artificial inorganic enzyme-free self-propelled microfish robot for selective detection of Pb2+ in water - Moo, James Guo Sheng (2014)
The availability of drinking water is of utmost importance for the world population. Anthropogenic pollutants of water, such as heavy-metal ions, are major problems in water contamination. The toxicity assays used range from cell assays to animal tests. Herein, we replace biological toxicity assays, which use higher organisms, with artificial inorganic self-propelled microtubular robots. The viability and activity of these robots are negatively influenced by heavy metals, such as Pb2+, in a similar manner to that of live fish models. This allows the establishment of a lethal dose (LD50) of heavy metal for artificial inorganic microfish robots. The self-propelled microfish robots show specific response to Pb2+ compared to other heavy metals, such as Cd2+, and can be used for selective determination of Pb2+ in water. It is a first step towards replacing the biological toxicity assays with biomimetic inorganic autonomous robotic systems.